The distinct spatiotemporal evolutionary landscape of HBV and HDV largely determines the unique epidemic features of HDV globally - Ding, Yibo; Guo, Hongbo; Hong, Xinfang; Li, Qiudi; Miao, Zhijiang; Pan, Qiuwei; Zheng, Kuiyang; Wang, Wenshi (Molecular phylogenetics and evolution, 2024)
[Display omitted] •Compared with HBV, HDV exhibited a distinct spatiotemporal distribution path.•The distinct spatiotemporal path fostered the current epidemic features of HDV.•The fitness to local HBV genotypes facilitates the geographical separation of HDV.•The fitness to human lineages promotes the genetic diversity of HDV.•HDV infections increased sharply after 1980s, warning of the disease ramp-up. Chronic infection of hepatitis B virus (HBV) and hepatitis D virus (HDV) causes the most severe form of viral hepatitis. Due to the dependence on HBV, HDV was deemed to co-evolve and co-migrate with HBV. However, we previously found that the naturally occurred HDV/HBV combinations do not always reflect the most efficient virological adaptation (Wang et al., 2021). Moreover, regions with heavy HBV burden do not always correlate with high HDV prevalence (e.g., East Asia), and vice versa (e.g., Central Asia). Herein, we systematically elucidated the spatiotemporal evolutionary landscape of HDV to understand the unique epidemic features of HDV. We found that the MRCA of HDV was from South America around the late 13th century, was globally dispersed mainly via Central Asia, and evolved into eight genotypes from the 19th to 20th century. In contrast, the MRCA of HBV was from Europe ∼23.7 thousand years ago (Kya), globally dispersed mainly via Africa and East Asia, and evolved into eight genotypes ∼1100 years ago. When HDV stepped in, all present-day HBV genotypes had already formed and its global genotypic distribution had stayed stable geographically. Nevertheless, regionalized HDV adapted to local HBV genotypes and human lineages, contributing to the global geographical separation of HDV genotypes. Additionally, a sharp increase in HDV infections was observed after the 20th century. In conclusion, HDV exhibited a distinct spatiotemporal distribution path compared with HBV. This unique evolutionary relationship largely fostered the unique epidemic features we observe nowadays. Moreover, HDV infections may continue to ramp up globally, thus more efforts are urgently needed to combat this disease.